Bioinformatics in the Post-Genomic Era
Biomedicine is one of the most important fields for the prospective applications of the information from human genome studies. However, there are many \\\\\\\\\\\\\\\'white spots\\\\\\\\\\\\\\\' in the present-day understanding of the biomedical implications of this information. Given that at least half of the proteins in the established sequence of the human genome have no annotation whatsoever and that the sequence similarity searches are not likely to produce any, definite research strategies to analyse the functions of these unknown proteins as well as other enigmatic aspects of the human genome are being elaborated. The elaboration of the logistics of these research strategies, of the relevant computational methodologies as well as the general management of the informational complexity of the biological systems belong to the main tasks for the post-genomic bioinformatics. This volume concentrates on the role of the biophysical studies and biophysical concepts that can assist the endeavour.